Prognostic value of alcohol consumption and some other dietary habits for survival in a cohort of Chinese men with lung cancer. Issue 1 (December 2017) - Li, Wentao; Tse, Lap; Au, Joseph; Yu, Kai; Wang, Feng; Yu, Ignatius
Abstract Background Alcohol consumption and some other dietary habits are thought to be associated with lung cancer incidence. However, the effects of these habits on lung cancer prognosis have been studied rarely. The purpose of this study was to address these gaps in knowledge. Methods We studied a cohort of 1052 Chinese men in Hong Kong who were diagnosed with primary lung cancer. Cox proportional hazards models were used to determine the prognostic values of consumption of alcohol, fresh fruits or vegetables, meat, and fried or preserved food. Results Compared with never drinkers, men who drank alcohol 1–3 days per week had a more favorable lung cancer prognosis (hazard ratio [HR]: 0.82, 95% confidence interval [CI] 0.68–0.97); however, this survival advantage was not significant in men who drank alcohol more frequently (HR: 0.91, 95% CI 0.73–1.14). Compared with men who consumed preserved or fried food only occasionally, men who consumed these foods frequently had a higher risk of lung cancer mortality (HR: 1.20, 95% CI 1.00–1.42). Conclusions Occasional consumption of alcohol was a favorable survival factor for Chinese men with lung cancer. However, this survival benefit did not exist for frequent drinkers of alcohol. Chinese men with lung cancer who were frequent consumers of fried or preserved food had a worse prognosis than those who consumed these foods only occasionally.